2018
DOI: 10.1292/jvms.18-0267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of somatotype in the reticulated giraffe (<i>Giraffa camelopardalis reticulata</i>) using three-dimensional laser measurement

Abstract: The giraffe (Giraffa camelopardalis) is a difficult animal to keep in captivity as it has high mortality due to nutrition-related disorders, perhaps because the giraffe’s condition is difficult to evaluate. Image analysis techniques have recently become popular and may be useful for evaluating the giraffe’s somatotype. The present study aimed to evaluate the giraffe somatotype using a three-dimensional laser measurement device, and to examine the usefulness of this method. First, ten zoo staff members visually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Although the dataset is obtained within a short time (1-2 min) and the laser instrument can be operated on a moving target, to obtain an accurate dataset, the animal should not move during measurements. Second, as described in our previous study, this technique does not directly evaluate the subcutaneous or visceral adipose tissue; thus, results might only reflect differences in skeletal structure [39]. In addition, in reticulated giraffe and okapi, the rumen volume due to recent feed intake may affect the results.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Although the dataset is obtained within a short time (1-2 min) and the laser instrument can be operated on a moving target, to obtain an accurate dataset, the animal should not move during measurements. Second, as described in our previous study, this technique does not directly evaluate the subcutaneous or visceral adipose tissue; thus, results might only reflect differences in skeletal structure [39]. In addition, in reticulated giraffe and okapi, the rumen volume due to recent feed intake may affect the results.…”
Section: Discussionmentioning
confidence: 90%
“…The present study adopted relative change rates and scatter plots to evaluate body shape and showed that both might become regular evaluation factors. As described in our previous study [39], the dataset obtained by the three-dimensional laser measurement technique varied among individual animals. Therefore, standardized evaluation factors not affected by individual size are required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations